СОЦІАЛЬНО-ЕКОНОМІЧНА ОРГАНІЗАЦІЯ ЗНАНЬ: СУТНІСТЬ ТА РОЛЬ У ФОРМУВАННІ ЛЮДСЬКОГО КАПІТАЛУ - Яременко, О. Л.; Носик, О. М. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The main characteristics of social and economic organization of knowledge as a set of controls movement of knowledge in society and the process of social selection, recognition of knowledge and mastery of them are revealed. The socialization of knowledge is a social process of their transformation in social knowledge is proved. The socio-economic organization of knowledge is a factor in the accumulation of human capital is proved, component of social capital.